Design and Development of Gateway Port Scanner - Aggarwal, Seema (My University, 2007)
In today’s enterprise environment hackers and intruders have made many successful attempts to bring down high-profile company networks and web services. Many methods have been developed to secure the network infrastructure and communication over the Internet, like the use of firewalls, encryption, and virtual private networks.. Using prevention systems, information can be collected from known types of attacks and find out if networks or hosts are being compromised. The information collected this way can be used to harden the network security, as well as it can be used to solve legal issues. Both commercial and open source products are available for this purpose. Many vulnerability assessment tools are available in the market that can be used to assess different types of security holes present in the network. In this Thesis the focus would be on open source network security tools. Open-source systems are not going to replace offerings from commercial vendors. They do, however, offer an increasingly viable alternative. Open-source solutions should be evaluated side-by-side with commercial as part of a tender process. Judged on their merits, open-source solutions may prove to be the best solution for many organizations.
Keywords: Network Security; Security Tool and Testing